Early postoperative intraperitoneal chemotherapy (EPIC) following cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in 632 patients with pseudomyxoma peritonei of appendiceal origin: A single institution experience. Issue 7 (July 2022) - Fung, Xavier; Li, I.Chuan; Chandrakumaran, Kandiah; Cecil, Tom; Dayal, Sanjeev; Tzivanakis, Alexios; Moran, Brendan; Mohamed, Faheez
Abstract: Background: There is ongoing controversy concerning the indications and benefits of early postoperative intraperitoneal chemotherapy (EPIC) following cytoreductive surgery (CRS) and hyperthermic intra-peritoneal chemotherapy (HIPEC) in patients with pseudomyxoma peritonei. The main contra-indications preventing wide-spread use of EPIC are reports of an increased postoperative morbidity with no clear evidence of oncological benefit. This paper reports a single high volume institution experience with EPIC over a 25-year period. Methods: This is a retrospective analysis of a single institution prospective database of patients undergoing CRS and HIPEC for appendiceal neoplasms from March 1994 to December 2019. Sub group analysis of patients who received EPIC with 5FU 15mg/m2 is reported and compared with patients who did not receive EPIC. Results: Overall, 632/1564 (40%) received EPIC. Patients who received EPIC were younger (median age 55 (IQR 45–63) vs 59 (IQR 50–68)) with similar extent of disease to those who did not have EPIC. EPIC was more likely to be given after complete cytoreduction. The use of EPIC has reduced over the last 25 years from 78% of patients initially to 16% most recently. Length of stay in critical care and total hospital stay were longer in patients who received EPIC but surprisingly major morbidity (Clavien Dindo Grade >3) was lower (p = 0.001). Conclusion: EPIC can be administered safely following CRS and HIPEC for PMP of appendix origin when used in carefully selected patients in a high-volume centre. Randomised trials are needed to establish impact on disease free and overall survival to optimize selection criteria. Abstract : Sypnosis: Early Postoperative Intraperitoneal Chemotherapy (EPIC) can be safely used in carefully selected patients in a high-volume centre following Cytoreductive Surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) with Pseudomyxoma Peritonei of appendiceal origin.